A case report of pediatric intestinal taeniasis presenting as severe anemia: a rare manifestation of taeniasis - Yacobus, Danny Jaya; Edina, Brenda Cristie; Tarigan, Ardanta Dat Topik; Nurmasithah, Nurmasithah; Ngasu, Natashya Philipa Ngada; Pradibdo, Ruth Clarita; Ratridewi, Irene (Paediatrica Indonesiana, 2026)
Taeniasis is a neglected tropical diseases that predominantly affects developing countries, including Indonesia. Although intestinal taeniasis can be diagnosed and treated in resource-limited settings, it is frequently underdiagnosed due to nonspecific clinical manifestations. Severe anemia is a rare complication of intestinal taeniasis.